Pengaruh Aromaterapi Lavender Terhadap Tingkat Kecemasan Ibu Hamil Menjelang Persalinan - Utama, Risma Putri; Suardi, Yunita Suriani (Barongko: Jurnal Ilmu Kesehatan, 2025)
Anxiety in pregnant women approaching labor is a psychological condition that often occurs and can have a negative impact on the labor process. Lavender aromatherapy is known to have a calming effect and can be used as a non-pharmacological intervention. This study aims to determine the effect of lavender aromatherapy on the level of anxiety in pregnant women approaching labor. The research method used was a quasi-experimental design with a pre-test and post-test with control group. The sample consisted of 30 pregnant women in the third trimester who were divided into intervention and control groups. The results showed a significant decrease in anxiety levels in the group given lavender aromatherapy compared to the control group. It can be concluded that lavender aromatherapy is effective in reducing anxiety levels in pregnant women approaching labor.